Analytical and numerical analysis of the torsional response of the multi-cell deck of a collapsed cable-stayed bridge. (15th August 2022) - Scattarreggia, Nicola; Galik, William; Calvi, Paolo M.; Moratti, Matteo; Orgnoni, Andrea; Pinho, Rui
Abstract: A relevant portion of the bridge over the Polcevera river in Genoa, widely known as the Morandi bridge, collapsed suddenly in August 2018, causing 43 casualties. While most initial forensic studies indicated that a cable-stay failure likely triggered the bridge collapse, only preliminary modelling of the ensuing flexural–torsional-shear failure of the bridge's deck has been undertaken to date. This paper extends previous work by (i) including the most up-to-date knowledge of the Morandi bridge's as-built geometry and reinforcement, (ii) performing detailed numerical studies of the bridge deck capacity, damage accumulation, failure modes, and reinforcement details, and (iii) comparing advanced numerical results with analytical methods to assess the prediction capabilities of simplified procedures for combined-load scenarios of multi-cell box girders. Concrete damage is numerically assessed with both the Finite Element Method and the Applied Element Method, both of which show damage migration for different reinforcement layouts, knowledge of which evolved throughout the forensic process. A numerical simulation of the failure kinematics is then compared against a frame-by-frame video recording of the collapse and a strong match is observed. Finally, a comparison between numerical strength predictions and analytical strength predictions shows that, even though the analytical procedures require significant simplification of the problem, they produce reasonable strength estimates when compared with the Finite Element approach.